Economic implications of the control of East Coast fever in eastern, central and southern Africa - Mukebi, A.W.; Perry, Brian D. (International Livestock Centre for Africa, 1993)
Considerable economic losses in the eastern, central and southern Africa region are caused by East Coast fever. The disease is conventionally controlled by acaricides and chemotherapy, however, these methods of control have become less reliable, acceptable and sustainable for a variety of reasons. These included the high cost of acaricides and drugs paid for in foreign currency, poor maintainance of dips or spray races, water shortages, acaricide resistance, illegal cattle movements, contamination of the environment or food with toxic residues and alternative tick hosts. New, safer, cheaper and more sustainable methods based upon immunisation are being developed. At present, the only available method of immunisation is the infection and treatment method. It is currently being applied in many countries of the region. This method shows considerable advantage over the current control methods and appears to be economically viable. Individual countries need to assess the efficacy of and appropriate policies for more widespread use of the method. ILRAD provides technical backup and collaborative socio-economic assessments of the application of the method in the affected region.